(untitled) (Asian Education Studies, 2022)
As an interdisciplinary study, legal English translation involves three fields: law, linguistics and translation. Accordingly, legal English research should adopt an interdisciplinary perspective, whereas the current domestic research often overemphasizes the external legal literacy and neglects the internal structure of legal language. Therefore, translators sometimes misinterpret the special semantics of legal English. From the perspective of cognitive linguistics, legal English’s special semantics is mainly reflected in legal vocabulary and legal texts. Firstly, based on the metaphor theory of cognitive linguistics, the research will focus on the differences between the original domain and the target domain of legal English vocabulary, and analyze the metaphorical expression in legal language; secondly, based on the fuzzy phenomenon of cognitive linguistics, the research will interpret specific legal English texts to clarify the ambiguities; finally, the research will explore the legal English translation strategies through the cognitive interpretation of legal language.